Difference in the salivary pH before and after consumption of vitamin C lozenge on preclinical student of Faculty of Dentistry Universitas Padjadjaran - Sopannata, Nirmala Trihasmana; Haroen, Edeh Roletta; Richata, Tuty Sutini (Universitas Padjadjaran, 2010)
Introduction: Vitamin C lozenge can increase pH saliva. Increasing saliva pH is cause saliva works as a buffer that can neutralize the acidity of vitamin C. The purpose of this research was to find the difference saliva pH before and after sucking vitamin C tablet. Methods: The research was carried out with quasi-experiment, using purposive sampling method and Paired t Test. This research was conducted on 30 students of the Faculty of Dentistry of Padjadjaran University, ranging 18-23 years of age. The research was carried out by measuring salivary pH before and after sucking vitamin C tablet. Results: Research result indicates that the average difference of salivary pH after sucking vitamin C tablet is 0.42 with standard deviation ±0,189. From statistic results T calc 12,282 > T table 2,05 Ho is rejected, H1 is accepted. Conclusion: The research conclusion shows that there is a significant difference on saliva pH before and after sucking vitamin C tablet lozenge on preclinical student of Faculty of Dentistry Padjadjaran University.